Harmonisasi Identitas Pribadi dan Pajak Melalui Pemadanan NIK dan NPWP dalam Pendampingan SPT Tahunan WPOP - Sari, Dian Purnama; Purwanto, Marini; Esa, Ariston Oki; Kristina, Natalia (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
This service activity was carried out with the aim of directly assisting the reporting of the 2022 annual SPT as well as matching ID Number with TIN for Individual Taxpayer. There is a difference with previous years because it was followed by the matching of ID Number as TIN. The implementation method is carried out directly and via zoom. This activity went well. The total number of participants accompanied was 31 Individual Taxpayer. Individual Taxpayer who are accompanied include permanent employees, freelancers and MSME entrepreneurs. The 2022 Annual reporting process for Individual Taxpayer is running smoothly. The problem with reporting that occurs is more towards the taxpayer's unpreparedness of data. However, some of the obstacles in matching ID Number as TIN are more related to population issues. For this population problem, taxpayers must take care of it themselves with relevant government departments. Activities to match ID Number as TIN should continue to be carried out bearing in mind that the implementation of ID Number as TIN will be carried out in full starting January 1, 2024.